Temporary markets: Market devices and processes of valuation at three Basel art fairs. (March 2023) - Haisch, Tina; Menzel, Max-Peter
We investigate trade fairs as markets. We combine literature on temporary clusters and that on the geography of markets and describe how the particular knowledge ecologies at trade fairs are enhanced by market devices. Our framework distinguishes the following three kinds of market devices: physical arrangements, judgement devices and prosthetic prices. Using this framework, we compare market constructions before, during and after three fairs for contemporary art in Basel. Our study presents the following findings. Firstly, the limited time and space at trade fairs lead to a proliferation of market devices. Secondly, different equipment with market devices leads to a hierarchy of fairs. Thirdly, trade fairs at the top of this hierarchy generate market devices for other temporary markets and thus contribute to the development of a uniform global market.